Implementação de um aplicativo móvel para a interação entre fiéis e suas paróquias - MORAES, Augusto Perez de; MONTECINO, Sara (121, 2022)
Objetiva-se neste projeto criar um aplicativo católico que ajude os fiéis a terem acesso fácil às informações da sua paróquia. Tendo esse acesso, os usuários leigos poderão exercer o seu dever como cristãos, a caridade, podendo auxiliar nas atividades de sua comunidade. Para a implementação do projeto foram utilizados o framework Flutter e o Backend-as-a-Service Firebase.

The aim of this project is to create a Catholic app, helping the faithful to have easy access to information about their parish. Having this access, lay people will be able to exercise their duty as a Christian, charity, being able to assist in the activities of their community. With the app, people who feel the need to help and do good will be able to see where they can be useful, with the dissemination of information about the needs of each pastoral. For the implementation of the project will be used the Framework Flutter and the Firebase database.
Implementation of a mobile application for interaction between parishioners and their parishes.
Keywords: aplicativos móveis; Catolicismo; Arquivos religiosos; Informação e Comunicação